Lived religion: the Rapai tradition through conflict and post-conflict in Aceh, Indonesia - Muhammad Maulana; Muhammad Hendri; Gustira Monita (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2026)
This study examines how religious meaning is publicly expressed and sustained through the Rapai, a communal frame-drum performance tradition from Aceh, Indonesia, and how its continuity across conflict and post-conflict periods reflects social resilience. Using a lived religion perspective, the article draws on qualitative document and visual analysis of publicly available materials, including textual, visual, institutional, and academic sources. The findings show that Rapai persisted through actions such as safeguarding instruments, maintaining intermittent performances during conflict, reorganising groups, and transmitting repertoire through schools, festivals, and community associations in the post-conflict era. These patterns indicate that Rapai operates as an embodied cultural-religious practice in which coordinated participation, devotional language, bodily discipline, and intergenerational learning support communal orientation during instability and recovery. The study analyses publicly documented expressions of lived religion rather than private religious experience. By situating the analysis in a Muslim-majority and post-conflict context, the article contributes to broader discussions of lived religion, cultural performance, and social resilience by showing how Rapai sustains religious memory, social ties, and communal orientation across conflict and post-conflict conditions. The article therefore treats Rapai as a public practice where art, devotion, memory, and communal discipline intersect in the work of surviving violence and rebuilding social life after the conflict in Aceh.